Quaternary nanocrystal solar cells - Cattley, C (2016)
This thesis studies quaternary chalcogenide nanocrystals and their photovoltaic applications. A temperature-dependent phase change between two distinct crystallographic phases of stoichiometric Cu2ZnSnS4 is investigated through the development of a one pot synthesis method. Characterisation of the Cu2ZnSnS4 nanocrystals was performed using absorption spectroscopy, transmission electron microscopy (TEM) and powder X-ray diffraction (XRD). An investigation was conducted into the effects of using hexamethyldisilathiane (a volatile sulphur precursor) in the nucleation of small (<7nm), mono-dispersed and solution-stable quaternary Cu2ZnSnS4 nanocrystals. A strategy to synthesize high quality thermodynamically stable kesterite Cu2ZnSnS4 nanocrystals is established, which subsequently enabled the systematic study of Cu2ZnSnS4 nanocrystal formation mechanisms, using optical characterization, XRD, TEM and Raman spectroscopy. Further studies employed scanning transmission electron microscopy (STEM) energy dispersive x-ray (EDX) mapping to examine the elemental spatial distributions of Cu2ZnSnS4 nanocrystals, in order to analyse their compositional uniformity. In addition, the stability of nanocrystals synthesised using alternative ligands is investigated using Fourier transform infrared spectroscopy, without solution based ligand substitution protocol is used to replace aliphatic reaction ligands with short, aromatic pyridine ligands in order to further improve Cu2ZnSnS4 colloid stability. A layer-by-layer spin coating method is developed to fabricate a semiconductor heterojunction, using CdS as an n-type window, which is utilised to investigate the photovoltaic properties of Cu2ZnSnS4 nanocrystals. Finally, three novel passivation techniques are investigated, in order to optimise the optoelectronic properties of the solar cells to the point where a power conversion efficiency (PCE) of 1.00±0.04% is achieved. Although seemingly modest when compared to the performance of leading devices (PCE>12%) this represents one of the highest obtained for a Cu2ZnSnS4 nanocrystal solar cell, fabricated completely under ambient conditions at low temperatures.